Implementation of a Web-based Digital Repository Information System at the Office of Sumbersekar Village - Meme Susilowati; Yudhi Kurniawan; Lilis Lestari Wilujeng (Journal of Community Practice and Social Welfare, 2022)
This research-based community service program is entitled Implementation of a Web-based Digital Repository Information System at the Office of Sumbersekar Village. This activity is motivated by the need to conduct collaborative learning programs with the village for the implementation of research results. Activities oriented towards product implementation as a more comprehensive effort for the downstream process of research results in the service carried out by private universities that can be utilized by the community. Down streaming the results of this research is also the basis for managing collaborative learning activities for the Independent Learning (as suggested by the term MBKM) between Ma Chung University and the village. The issue of the village's desire to switch from a manual system to a computerized system is our focus. In the transition process from manual to computerized system, many information systems are needed, one of which is data digitization. Digitizing the repository allows centralized data so that the village staffs will find them easier to search when needed. Centralized storage media can support verification, namely the process of checking, confirming, and ensuring archives, ensuring the legality and integrity of related files and their relationship to the village. The repository information system implemented at the village office is expected to minimize archiving errors, facilitate data retrieval, avoid lost or damaged documents, and can anticipate data theft. This repository information system also facilitates the process of monitoring, controlling, as well as backing up data. Therefore, this community service has successfully implemented a repository information system for internal village documents.